THE MODULATORY ACTION OF TARAXACUM OFFICINALE ON THE GLUTATHIONE SYSTEM - Ala FULGA; Svetlana PROTOPOP; Lilia ANDRONACHE; Olga TAGADIUC (Academy of Sciences of Moldova, 2022)
The evaluation of the antioxidant activity of plants has been an important issue taking into account its importance on human health. Natural antioxidants protec t cells against oxidative stress, which can damage the cellular components. Taraxacum officinale (TO) leaves (TOL) and roots (TOR) has been commonly used in traditional medicine due to biologically active ingredients. This plant is rich in substances with high antioxidant activity (flavonoids, phenolic acids, coumarins, vitamins etc.). Glutathione represents the most abundant thiol of cells with important functions in the antioxidant system. Until now, there are no comprehensive data about TO extracts action on glutathione content.The objective of the study was to report the influence of TOL and TOR ethanolic extracts on the glutathione content of erythrocytes. TOL and TOR were harvested from a natural habitat of Republic of Moldova. The dry plants were extracted using ethanol as solvent (10, 20, 25, 40, 50 and 80% (v/v)). As source of glutathione were red blood cells (RBC) of healthy persons. As a result we determined that TO exhibits a modulatory action on glutathione content. The highest (28.03±1.14 µM/g. Hb) content of GSH was determined due to action of roots extracts made on ethanol of 20%, the lowest (10.88±0.83 µM/g. Hb) in case of leaves extracted on alcohol of 20%. Opposite, the lowest (5.92±0.72 µM/g. Hb) amount of GSSG was determined as a result of action of radicular extracts made on ethanol of 20%. The highest (11.46±3.27 µM/g. Hb) concentration of GSSG was determined by influence of roots extracts on ethanol of 50%.In conclusion, Taraxacum officinale exhibits a strong antioxidant activity. This plant has ability to prevent and treat the damage of cells caused by oxidative stress process, by actioning on glutathione system. This activity depends of ethanol concentrations and plant's part.